Respostas
respondido por:
0
x/6 = (x+3)/5 (mmc de 5 e 6 = 30 então multiplico todos por 30 )
30x/6 = 30(x+3)/5
5x = 6(x+3)
5x = 6x + 18
- 18 = 6x - 5x
x = -18 ok
30x/6 = 30(x+3)/5
5x = 6(x+3)
5x = 6x + 18
- 18 = 6x - 5x
x = -18 ok
respondido por:
0
x/6 = (x+3)/5
5x = 6.(x+3)
5x = 6x+18
5x-6x = 18
-x = 18 .(-1)
x = -18
5x = 6.(x+3)
5x = 6x+18
5x-6x = 18
-x = 18 .(-1)
x = -18
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás